(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Portal hypertension is an increase in the blood pressure within the system of veins called the Hepatic portal venous system. Veins coming from the stomach, intestine, spleen, and pancreas merge into the portal vein, which then branches into smaller vessels and travels through the liver. If the vessels in the liver are blocked due to liver damage, blood cannot flow properly through the liver. As a result, high pressure in the portal system develops. This increased pressure in the portal vein may lead to the development of large, swollen veins (varices) within the esophagus, stomach, rectum, or umbilical area (belly button). Varices can rupture and bleed, resulting in potentially life-threatening complications. We present a case of portal hypertension with massive ascites- A 43-year-old female was admitted with chief complaints of abdominal distension, abdominal pain, and shortness of breath prior to 15 days of presentation and the symptoms were gradually progressive in nature. Her past medical history reveals she had similar complaints in the past and known cases of chronic liver disease. After admission, she has been diagnosed with portal hypertension along with Refractory ascites. The management included antihypertensives and human albumin, A high protein diet with salt and fluid restrictions, large-volume paracentesis procedure was carried out daily.